A Borel linear subspace of R^ω that cannot be covered by countably many closed Haar-meager sets - Banakh, Taras; Jabłońska, Eliza (Topological Methods in Nonlinear Analysis, 2024)
We prove that the countable product of lines contains a Haar-null Haar-meager Borel linear subspace $L$that cannot be covered by countably many closed Haar-meager sets.This example is applied to studying the interplay between various classes of ``large''sets and Kuczma-Ger classes in the topological vector spaces ${\mathbb R}^n$ for $n\le ω$.